Prison health service directors' views on research priorities and organizational issues in conducting research in prison: Outcomes of a national deliberative roundtable - Simpson, P.; Guthrie, J.; Butler, Tony (Taylor and Francis, 2017)
© 2017 Emerald Publishing Limited. Purpose-Given that prisoners have significant health needs across most areas, the paucity of prisoner health research, and the difficulties involved in the conduct of research in this setting, there is a need to develop research priorities that align with key stakeholder groups. One such group are those responsible for health service provision in prisons-prison health service directors. The paper aims to discuss these issues. Design/methodology/approach-Prison health service directors in each Australian state and territory were invited to participate in a national (deliberative) roundtable where the consensus building nominal group technique was utilized. This involved the identification of research priorities and organizational issues in conducting research with prisoners, and ranking research priorities. A thematic analysis was conducted on organizational issues. Findings-In total, 13 participants attended the roundtable. Participants identified 28 research priorities and 12 organizational issues. Top ranked research priorities were mental health, cognitive and intellectual disability, post-release health maintenance, ageing prisoners, chronic health conditions and Aboriginal and Torres Strait Islander health. Themes identified from the organizational issues included prisoner access to research participation, health and research literacy of custodial staff, and institutional protectionism in response to research that may discover negative information about the custodial setting. Research limitations/implications-These findings should inform future efforts to improve research infrastructures to undertake research to improve the health of people in Australian prisons, and help to align researchers' efforts with those of a key organizational stakeholder. Originality/value-This is the first paper to determine the research priorities and organizational issues in conducting research in prisons of prison health service directors.